تقدير شدة الجفاف الفصلي والسنوي وتكراره في بعض مواقع المنطقة الجنوبية من سورية - جـلب أدهـم; شيخو طاهر (Latakia University Journal -Biological Sciences Series, 2012)
يعد الجفاف ظاهرة متكررة وسمة طبيعية للمناخ، وأحد المخاطر الطبيعية الكبرى التي تتعرض له سورية بشكل متكرر ملحقاً أضراراَ كبيرة بالنظم البيئية والاجتماعية - الاقتصادية، وخاصة المناطق الزراعية. تهدف هذه الدراسة إلى تقدير شدة الجفاف وتكراره على المستويين الفصلي والسنوي في المنطقة الجنوبية من سورية، بتطبيق مؤشر الهطل القياسي (SPI) على البيانات المطرية المسجلة خلال الفترة (1958 - 2006) في أربع محطات مناخية هي دمشق، خرابو، درعا والسويداء. أظهرت النتائج عدم وجود تغيرات أو اتجاهات معنوية في كميات الأمطار السنوية والشتوية والربيعية على مستوى منطقة الدراسة، وتعرضها إلى حوادث الجفاف بشكل متكرر. وتميزت محطتا دمشق وخرابو على المستوى السنوي عن باقي المحطات بالجفاف المتطرف، وخرابو بالجفاف الشديد. وتميز فصل الربيع بأنه الأكثر تعرضاً لحوادث الجفاف، يليه فصلا الشتاء والخريف. كما لوحظ غياب الجفاف الشديد عن شتاء درعا، والجفاف المتطرف عن خريف دمشق وخرابو. Drought is a recurrent phenomenon and a normal feature of climate. It is one of the major natural hazards that frequently hits Syria, causing significant damages to ecosystems and social–economic environment, especially agricultural areas. The purpose of current study is to estimate the degree of severity and the frequency of drought at seasonal and annual timescales in the southern region of Syria by applying the Standardized Precipitation Index (SPI) on the rainfall data recorded over (1958-2006) in four climatic stations: Damscus, Khrabo, Dara and El-Sweda. The results showed that there were no significant changes or trends in annual winter and spring rainfall at southern region scale. They also showed its frequent exposure to drought. At annual timescale, Damscus and Khrabo stations were distinguished from the others by extreme drought, and Khrabo by severe drought. The season mostly exposed to drought events was spring, followed by winter and autumn seasons. The absence of the evere drought of Dara winter, and the extreme drought of Damscus and Khrabo autumn were also observed.